Antigen-Specific Priming is Dispensable in Depletion of Apoptosis-Sensitive T Cells for GvHD Prophylaxis - Yarkoni, Shai (Frontiers Media S.A., 2014)
Prophylactic approaches to graft versus host disease (GvHD) have employed both phenotypic reduction of T cells and selective elimination of host-primed donor T cells in vitro and in vivo. An additional approach to GvHD prophylaxis by functional depletion of apoptosis-sensitive donor T cells without host-specific sensitization ex vivo showed remarkable reduction in GHD incidence and severity. We address the role and significance of antigen-specific sensitization of donor T cells and discuss the mechanisms of functional T cell purging by apoptosis for GvHD prevention. Host-specific sensitization is dispensable because migration is antigen-independent and donor T cell sensitization is mediated by multiple and redundant mechanisms of presentation of major and minor histocompatibility complex and tissue antigens by donor and host antigen-presenting cells. Our data suggest that potential murine and human GvH effectors reside within subsets of preactivated T cells susceptible to negative regulation by apoptosis prior to encounter of and sensitization to specific antigens.